Trumped Up Charges: Empirical Effects of U.S. Immigration Reform on Crime and Jobs - Bohn, Sarah (2015)
This brief examines the effects, both intended and unintended, of two previous efforts to deter and regulate unauthorized immigration. Recent research shows that the Immigration and Reform Act of 1986, by cutting off access to legal employment for undocumented immigrants, actually increases the probability that some people who are not in the country legally will engage in crime. And despite heightened efforts to police and deport undocumented immigrants in accordance with Section 287(g) of the Immigration and Nationality Act, studies indicate that any resultant decreases in immigrant populations did nothing to improve employment opportunities for low-skilled native residents. While past research reveals some of the limitations and unintended negative impacts of laws aimed at making the U.S. less attractive to unauthorized immigrants, less is known about the potential positive impacts of laws aimed at inclusion. Such knowledge could help to enlighten future debates over comprehensive reform.https://repository.upenn.edu/pennwhartonppi/1029/thumbnail.jp